Understanding and Optimizing Family Caregiver Participation in Dyadic Research. Issue 6 (1st November 2022) - Irani, Elliane; Mogle, Jacqueline; Durante, Ángela; Juárez-Vela, Raúl; Vellone, Ercole; Buck, Harleah G.
Abstract : Background: Research to understand self-care behaviors increasingly engages patient–caregiver dyads. However, collecting data on dyads requires both members to complete the research protocol, potentially resulting in biased information if caregivers who do not participate differ from caregivers who do. Objectives: The aim of the study was to examine how recruitment conditions and patients' appraisal of dyadic engagement in heart failure management are related to caregiver participation across two research studies. Methods: We used logistic regression to examine whether recruitment strategy and patients' responses on the dyadic symptom management-type instrument were associated with caregivers' participation. Results: Caregivers not present at the initial recruitment were less likely to participate in the study. Regardless of recruitment strategy, caregivers were less likely to participate if the patient indicated primary responsibility for heart failure management. In the restricted recruitment study (recruiting both dyad members simultaneously), caregiver participation was significantly higher when patients selected a collaborative-oriented care type relative to patient- or caregiver-oriented type. Discussion: Instruments assessing dyad-level information could aid researchers in deploying resources at recruitment, as well as in adjusting results for data that could bias results and conclusions. Our findings support the importance of considering the recruitment strategy as well as dyadic care type as part of the recruitment process.